2017
DOI: 10.1016/j.clinph.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

We could predict good responders to vagus nerve stimulation: A surrogate marker by slow cortical potential shift

Abstract: 論文題目We could predict good responders to vagus nerve stimulation: a surrogate marker by slow cortical potential shift (脳波の緩電位変化は迷走神経刺激療法の治療効果の代替マーカーとなる) (論文内容の要旨) Objective: Vagus nerve stimulation (VNS) is a palliative treatment option for patients with intractable epilepsy who are not good candidates for surgical resection. The stimulation of the vagus nerve is intermittent, and the usual stimulation condition is set to a signal on-time (VNS ON) of 30 s followed by an off-time (VNS OFF) of 3-5 min repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Finally, Bayasgalan et al investigated SCPs as markers of VNS response 38 . Positive SCPs seen on EEG represent inhibitory postsynaptic potentials and inhibition of neuronal activity, and their production has been associated with seizure suppression 38 . Using EEGs with a 10‐second time constant, they reported that positive‐polarity SCPs are associated with good VNS response.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Bayasgalan et al investigated SCPs as markers of VNS response 38 . Positive SCPs seen on EEG represent inhibitory postsynaptic potentials and inhibition of neuronal activity, and their production has been associated with seizure suppression 38 . Using EEGs with a 10‐second time constant, they reported that positive‐polarity SCPs are associated with good VNS response.…”
Section: Resultsmentioning
confidence: 99%
“…But we still found that unilateral IEDs were perhaps predictors of good response to VNS, which agrees with Arcos et al [38], who considered that a temporal lobe discharge on the video-EEG was an indicator of an early response. Besides IEDs, the other EEG features, also reported as effective predictors for good response to VNS, included positive polarity of slow cortical potential (SCP) shifts on scalp EEG [39], the increase in P300 amplitude [40], lower global synchronization levels in delta and alpha frequency bands [41], ictal synchronization of brain activities measured with scalp EEG [42], and decreased connectivity with SEEG signals [43]. Conversely, Barbella et al [44] found no changes in epileptiform activity or in its localization in responders or non-responders, so more studies are needed that focus on the relation between EEG and the outcome of VNS in the future.…”
Section: Discussionmentioning
confidence: 99%
“…They all participated in our previous study and their clinical characteristics were described in detail. 9 At the last follow-up visit (mean 24.1, range 11.7-43.0 months), 12 patients became seizurefree. Patient demographics are briefly described in Table S1.…”
Section: Participantsmentioning
confidence: 97%
“…In a previous study, 9 we examined VNS-induced slow cortical potentials (SCPs) in patients with epilepsy and found an association between the presence of SCPs and seizure reduction, suggesting that alterations on electroencephalography (EEG) because of VNS reflect the efficacy of VNS against seizures. Because SCPs reflect repetitive firing of cortical neurons during VNS, SCPs from specific brain areas may be involved in the suppression of seizures.…”
Section: Introductionmentioning
confidence: 99%